2017
DOI: 10.1177/1358863x17740993
|View full text |Cite
|
Sign up to set email alerts
|

How to become proficient in performance of the resting ankle–brachial index: Results of the first randomized controlled trial

Abstract: The resting ankle-brachial index (ABI) is a first-line test to diagnose peripheral artery disease (PAD). No randomized controlled trial (RCT) has yet been conducted to determine the best teaching method to become proficient in the ABI procedure. We conducted a monocentric RCT to determine whether didactic learning alone or didactic learning combined with experiential learning improved proficiency in the ABI procedure. Medical students ( n = 30) received didactic learning, including (i) a presentation of the AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Given the importance of ABI in screening for PAD but also for CVD especially in asymptomatic patients, it is important for vascular physician to know ABI measurement and its interpretation, but above all it requires technical learning to obtain expertise from the beginning of medical studies and to optimize patient care. Previous study of our group has shown in a first randomized trial that didactic learning alone is insufficient to gain proficiency in the ABI procedure and combining didactic learning with experiential learning significantly improved the students' proficiency (5) . Moreover, Wyatt et al have defined a scoring sheet (Wyatt's score) to assess the proficiency in performance of the ABI (6) (Figure 1…”
Section: Introductionmentioning
confidence: 76%
“…Given the importance of ABI in screening for PAD but also for CVD especially in asymptomatic patients, it is important for vascular physician to know ABI measurement and its interpretation, but above all it requires technical learning to obtain expertise from the beginning of medical studies and to optimize patient care. Previous study of our group has shown in a first randomized trial that didactic learning alone is insufficient to gain proficiency in the ABI procedure and combining didactic learning with experiential learning significantly improved the students' proficiency (5) . Moreover, Wyatt et al have defined a scoring sheet (Wyatt's score) to assess the proficiency in performance of the ABI (6) (Figure 1…”
Section: Introductionmentioning
confidence: 76%
“…Thirdly, it was not possible to assess the reliability of the tests in this study. We do not have our own reliability for the exercise tests but the intra-observer coefficient of variation (CV) for the ABI at rest in our vascular laboratory is 9.4% (typical error of the estimate is 0.06) 36 . Furthermore, the reliability of the exercise tests has been previously reported by several studies: i) Van Langen et al showed that the inter-observer variability of the post-exercise ABI was 21% 37 ; ii) intra-test and test-retest reliability of exercise TcPO2 using a similar protocol that we used has been reported by Abraham and colleagues as excellent 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, dans certaines populations comme chez les diabétiques, les insuffisants rénaux, et les personnes âgées notamment, l'IPS de repos peut être faussement normal [5]. Dans ces cas et compte tenu des difficultés d'apprentissage, l'évaluation des flux Doppler peut apparaître comme intéressante [7][8][9][10]. Ainsi, l'artériopathie des membres inférieurs peut être définie au repos par [3,6,11]:…”
Section: Introductionunclassified